Obstructive sleep apnea in children: prevalence and association with overweight and obesity - Ingolfsdottir, Ingibjorg; Hrolfsdottir, Laufey; Johannesdottir, Groa Bjork; Halldorsson, Thorhallur Ingi; Magnusdottir, Solveig; Hallgrimsdottir, Erla Guðbjorg; Birkisson, Magnus; Petersen, Hannes (Frontiers in Sleep, 2026)
IntroductionObstructive sleep apnea (OSA) is an underdiagnosed health condition and in young children, if untreated, may have negative effects on mental and physical health. Although in adults obesity is recognized as a major risk factor for OSA in adults, the association between weight and OSA has not been as well documented in children. This study was conducted to evaluate prevalence of OSA in young children and if there is an association with weight gain, overweight and/or obesity.MethodsCross-sectional study, conducted over period of one-year in young children (4–9 years old) which included 29% (n = 371) of young children 4–9-years old this age group living within the general population in the recruitment area. Sleep was evaluated subjectively with the pediatric-sleep-questionnaire (PSQ) and objectively using a home sleep test. Two-nights of >4-h of sleep-duration was required for diagnosis of OSA. Overweight and obesity was evaluated using BMI z-score. Multivariable log-binomial regression analysis was used to assess the relationship between OSA and overweight/obesity. The analyses were adjusted for age, sex, history of asthma/allergies and prior adenotonsillar surgery.ResultsUndiagnosed OSA is prevalent in young children or 22.7%; with prevalence of moderate-OSA 16.2% and severe-OSA 6.5%. Each 1 (one) unit increase in BMI z-score was associated with 1.35-times (CI95%:1.22, 1.50) higher risk of having moderate/severe OSA. Childhood overweight (RR = 2.71; CI95%1.76, 4.16) and obesity (RR = 2.80; CI95%1.75, 4.49) were associated with almost 3 (three) times higher risk of having moderate/severe OSA. When analyzing BMI z-score from 18 months of age to current age (ΔBMI z-score), each 1 BMI z-score increase was associated with 1.24-times (CI95%: 1.08, 1.41) higher risk of having moderate/severe OSA.ConclusionsThe prevalence of OSA in young children is higher than previously reported. With weight gain, overweight, and obesity were strongly associated with OSA diagnoses.